Cardiopulmonary Resuscitation (CPR) Success Rates in Prehospital Settings: A Review of EMT Interventions - Khaled Sweileh Raddad Al-Rubaie; Khalid Moeid A Al Harthi; Mansour Faleh Farraj Alotaibi; Bader A Masfir Al Otaibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Typically, in the majority of individuals experiencing cardiac arrest outside of a hospital setting, cardiopulmonary resuscitation (CPR) is begun by first responders such as non-transporting firemen or police, or by emergency medical service (EMS) workers. The disparity in survival results between CPR initiation by first responders and EMS remains uncertain. Aim of work: To explore the emergency medical technicians (EMT) interventions and success rates of cardiopulmonary resuscitation (CPR) in prehospital settings. Methods: The keywords ”emergency medical technicians, EMT, interventions, success, rates, cardiopulmonary, resuscitation, CPR, prehospital settings" were used to conduct a thorough literature search in the MEDLINE database in order to find relevant publications published between 2017 and 2024. Using the proper search terms, Google Scholar was utilized to find and access pertinent scientific publications. Various inclusion criteria were used to choose which articles to select. Results: The research included in this study were published from 2017 to 2024. The research included a discussion segment that was broken into many specific elements. Topics covered include the Current CPR Guidelines, CPR and Prehospital Success and EMT intervention for CPR. Conclusion: The American Heart Association (AHA) has stressed the significance of high-quality chest compressions and prompt defibrillation in the resuscitation of cardiac arrest. The AHA strives for a chest compression percentage of 60%. However, there are other methods available, including as intraosseous access, supraglottic blind insertion airway devices, and hands-on defibrillation, which may further enhance results. Team-focused CPR (TFCPR) has been used to optimize the process of reviving patients experiencing cardiac arrest in prehospital settings. Nevertheless, the survival rates for patients who are outside of the hospital are lower than the global average, which highlights the need for enhanced regulations and training. The management of the airway during cardiac arrest is a subject of debate, since there is minimal evidence available from hospital settings. The findings from studies comparing bag-valve-mask ventilation with advanced airway placement have been inconclusive.